Quaternary Vertebrates of Québec: a Summary - Harington, C. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThe only representative of the extinct North American megafauna known from Québec is an American mastodon from Pointe de Chambord, Lac-Saint-Jean. Marine mammals have played a prominent part in our knowledge of the Quaternary vertebrates of Québec since Per Kalm was informed of a whale skeleton found inland from the St. Lawrence River about 1749. Five species of whales particularly adapted to inshore conditions have been reported from Late-glacial deposits of Champlain Sea age. The bones represent mainly white whales, but also narwhals, harbour porpoise, humpback, common finback and bowhead whales. Seals (ringed, harp, bearded and harbour) have also been discovered, and walrus remains are known from Sainte-Julienne-de-Montcalm and Saint-Nicolas. Sandpits at Saint-Nicolas (bottom-dwelling fishes, seabirds, ringed seal and white whale) and Saint-Césaire (fish, eider duck, ringed seal and white whale) have yielded important Champlain Sea vertebrate fossils, as well as paleoenvironmental information. Many well-preserved vertebrate remains have been found in calcareous nodules from Eardley and Breckenridge in the Gatineau area. Perhaps cave faunas will become increasingly important in sorting out the Quaternary vertebrate faunal sequence in Québec. The finds from caves near Saint-Elzéar and La Rédemption in Gaspésie, as well as Mine and Laflèche caves in the Gatineau region have already yielded fascinating insights. A list of radiocarbon dates on Quaternary vertebrates from Québec is provided.